PENINGKATAN EKONOMI DAN PEMBERDAYAAN MASYARAKAT PAMULANG BARAT MELALUI BUDIDAYA TANAMAN ANGGUR DAN SAYURAN - Katri Widayani; Mutiara eka Puspita; Afina Putri Vindiana; Muhammad Isa Aryakusuma; Langgeng Prasetyo Jati (Jurnal Abdi Insani, 2023)
There has been a decrease in the income of the people of West Pamulang, which was caused by the COVID-19 pandemic and the imposition of continuous activity restrictions causing a reduction in income. From these problems, the community must have the skills and knowledge needed to survive. One thing that can be done is to utilize unproductive land so that it can produce something that has economic value. One of them is grape cultivation. From the description above, the knowledge and skills needed include grape cultivation, hydroponic systems, knowledge of product quality management, marketing and financial systems to knowledge of agro-tourism and how to manage it so that it is successful. On this issue, community service activities are made as a channel of knowledge and skills from lecturers and students of the Indonesian Institute of Technology to the people of West Pamulang. A participatory approach by looking at local potential is chosen so that it is easily accepted by the community. In addition, community formation was also chosen to facilitate coordination and transfer of knowledge to the community. From the community side, the resulting output is an increase in knowledge, the provision of Appropriate Technology equipment that supports the cultivation and management of Agro-tourism. The team has created a logo and branding so that the Pamulang wine village can be recognized as well as marketing media in the form of a website that makes it easier for people to market and make purchase transactions. As for the government, this is in accordance with the vision and mission of the West Pamulang district head who wants to promote wine as a local commodity. The outcome of this activity in the future has the potential to increase income potential in the Pamulang Barat wine village community.